Entrepreneurial Mindset and its Impact on Marketing Ambidexterity an Applied Study on Small and Medium Enterprises in Baghdad - Yasir, Mohammed Hameed; Salman, Rafid Mohammed; Jaffar, Dr. Zaid Abdulzahra; Mahdi, Dr. Mohammed Saleh (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
The main objective of the current study is to determine the direct and indirect impact of the dimensions of entrepreneurial mindset (innovation, Pro-activeness, quick action / alertness, creativity) in achieving marketing ambidexterity in its dimensions (exploration, exploitation, marketing flexibility). This work used the statistical analysis method and the descriptive analytical method., the nature of relationships between the study variables was reached, and then the hypotheses were tested. Using the questionnaire form, primary data was collected from a random sample of (173) employees of companies for small and medium enterprises in Baghdad, Iraq. The study found significant relationships between the dimensions of entrepreneurial mindset and marketing flexibility. The study showed the importance of entrepreneurial mindset in achieving marketing ambidexterity in stimulating the behavior of managing small and medium enterprises to achieve competitive advantage.